Understanding the Appeal of Local Cosmetics of Mustika Ratu Cosmetics in Shaping Indonesian Generation Z Purchase Intentions - Annisa, Nur; Hanafiah, Ali (Jurnal Ilmiah Manajemen dan Bisnis, 2024)
Indonesia is a promising market for cosmetics and personal care products, providing opportunities for domestic and international manufacturers. The Indonesian cosmetics market is estimated to have reached around US$8.8 billion in 2021 and is expected to continue growing. One of the prominent local cosmetic companies is PT Mustika Ratu Tbk, which is renowned for its natural-based beauty products that combine traditional Indonesian ingredients with modern technology. However, Mustika Ratu faces challenges in maintaining its market position, particularly among Generation Z consumers, who represent a significant and growing demographic in Indonesia. This study aims to examine the factors influencing the purchase intention of Mustika Ratu's products among Indonesian GenZ, focusing on brand image, product quality, and price perception. Using a quantitative approach, data were collected through structured questionnaires from 168 respondents in the Jabodetabek area and analyzed using Partial Least Square (PLS) software version 3.2.9. The results of this study indicate that Brand Image, Product Quality, and Price Perception has a positive and significant influence on purchase intention of Mustika Ratu cosmetic products in Indonesian Generation Z.